NbThermo: a new thermostability database for nanobodies. (12th April 2023) - Valdés-Tresanco, Mario S; Valdés-Tresanco, Mario E; Molina-Abad, Esteban; Moreno, Ernesto
Abstract: We present NbThermo—a first-in-class database that collects melting temperatures ( T m ), amino acid sequences and several other categories of useful data for hundreds of nanobodies (Nbs), compiled from an extensive literature search. This so-far unique database currently contains up-to-date, manually curated data for 564 Nbs. It represents a contribution to efforts aimed at developing new algorithms for reliable T m prediction to assist Nb engineering for a wide range of applications of these unique biomolecules. Nbs from the two most common source organisms—llama and camel—show similar distributions of melting temperatures. A first exploratory research that takes advantage of this large data collection evidences that understanding the structural bases of Nb thermostability is a complex task, since there are no apparent differences in sequence patterns between the frameworks of Nbs with lower and higher melting temperatures, indicating that the highly variable loops play a relevant role in defining Nb thermostability. Database URL https://valdes-tresanco-ms.github.io/NbThermo